ANALISIS KINERJA PEGAWAI DI KECAMATAN GUNUNGPATI KOTA SEMARANG - Sukmarwati, Armediana; Suryaningsih, Margaretha; Dwimawanti, Ida Hayu (Journal of Public Policy and Management Review, 2013)
Employee performance problems can be inferred from the existence of the office at a time when employees are out of work hours with personal interests . Lack of discipline from the initial field observations suggest that in the district of Semarang Gunungpati there are still some employees who do not come right time.In addition there are also employees who can not do the work in accordance with the targets that have been seen ditentukan.Rendahnya employee discipline level of employee go to work ( at 08.00 pm ) and return home early ( before 14:15 hours GMT) from the provisions comes to work at 7:15 pm and return at 15:15 pm . Decrease in employee discipline characterized by the presence of morning and afternoon rally . these provisions are stipulated in Government Regulation No. 53 on Employee Discipline . Performance is not running optimally for pushing me to do this research .The research problem is : Why is the performance of employees in the District Gunungpati not optimal ? Factors what is the bottleneck of the performance of employees in the District Gunungpati Semarang ? To answer the problem and the research objectives using Mangkunagara , ( 2007:14 ) , employee performance is influenced by three factors , namely : individual factors , psychological factors , organizational factors , there are also factors that defined Rival Rival ( 2003:317 ) as a factor that can hinder performance , in this case Rival defines a three (3 ) main groups : legal 1.Kendala / legal.2.Bias penilai.3.Pengaruh assessment pribadi.4.Kesalahan opinion that tends terpusat.5.Gaya judgment in evaluating the performance . study was to use domain analysis techniques and technical analysis scorecard.Terdapat two sources of data used are primary data and the use of techniques sekunder.Penelitian depth interviews , observation , and documentation , as well as literature list of questions relating to the performance of employees in the district Gunungpati data.Berdasarkan collect the results showed that the performance of the mountain district employees including superior starch , can be seen from several phenomena that exhibit superior performance , namely compliance with government regulations the performance assessment , performance appraisal format Gunungpati in Semarang district , sanction violations given performance , the influence of personal opinion about the performance appraisal district Gunungpati in Semarang city , the errors tend to focus on performance in the district Gunungpati , leadership styles in evaluating the performance of employees in the city of Semarang district Gunungpati , training , feedback , performance appraisal techniques are appropriate . It is also supported by the results of the scorecard ( 3.4 ) including the superior category . However, there is also a phenomenon that has a value that is slightly less background and demographic this is because each of the employees is less ideology and understand the role of the work should be done and the circumstances surrounding that sometimes less support , but it can inadvertently affect their performance.